2000
DOI: 10.1346/ccmn.2000.0480507
|View full text |Cite
|
Sign up to set email alerts
|

Bleaching Properties of Alumina-Pillared Acid-Activated Montmorillonite

Abstract: Abstract--The bleaching of cottonseed oil by alumina-pillared (Al-pillared) acid-activated clays was investigated. Acid activation of a Ca-rich montmorillonite (CMS STx-I) following treatment with 1, 4, and 8 eq/L sulfuric-acid solutions, as well as subsequent pillaring with alumina, produces new materials. These materials have bleaching properties dependent upon the extent of activation of the clay prior to pillaring. The pillared acid-activated montmorillonites possessed higher bleaching efficiency compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 43 publications
2
19
1
Order By: Relevance
“…1 It shows bleaching action 2,3 and also can be effectively used as adsorbent for adsorption of harmful substances like dye 4,5 , heavy metal ions 6,7 from their sources. Its adsorption capacity as adsorbent and bleaching action can be increased manifold if it is activated particularly with acid.…”
Section: Introductionmentioning
confidence: 99%
“…1 It shows bleaching action 2,3 and also can be effectively used as adsorbent for adsorption of harmful substances like dye 4,5 , heavy metal ions 6,7 from their sources. Its adsorption capacity as adsorbent and bleaching action can be increased manifold if it is activated particularly with acid.…”
Section: Introductionmentioning
confidence: 99%
“…It can be inferred that the acidity was increased on increasing the Al loading on hexagonal mesoporous silica content. Falaras et al 9 reported that adsorption phenomenon in cottonseed oil is mainly involves the pigment such as gossypol, carotene and so on; the pigment attraction to the acid sites in the adsorbent.…”
Section: Resultsmentioning
confidence: 99%
“…In order to efficiently removal gossypol from cottonseed oil, a number of studies have been carried out, usually through caustic reining 7 and adsorption on solids, such as activated alumina 8 and activated montmorillonite-containing clays 9 . Richard et al 10 investigated that aluminas and silicas as adsorbents for reducing the gossypol from cottonseed oil, they found gossypol has a high affinity for alumina surface.…”
Section: Introductionmentioning
confidence: 99%
“…Through this process, the appearance of oil product can be improved. Its color becomes clearer and its production stability might be improved (Falaras, 2000). Bleaching earth can also remove chlorophyll, carotenoids, phosphorlipids, metals.…”
Section: Introductionmentioning
confidence: 99%